Gambaran Pola Makan Mahasiswa Jurusan Ilmu Gizi di Kepulauan Riau - Citra Dewi Anggraini; Herviana Herviana; Siska Pratiwi; Made Tantra wirakesuma (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Diet is information that defines eating patterns as well as the types of food consumed on a daily basis. Individual health status will be influenced by the use of a healthy diet. Inaccuracy in establishing regular meal routines also adds to imbalanced nutritional intake. The objective of this research is to describe dietary habits of nutritional students in Kepulauan Riau. This study was cross sectional study approach in October – November 2022. The population in this study is nutritional students (17 – 24 years old) in Kepulauan Riau as amount 50 subject. Data collection using a questionnaire by google form. The result of this study showed that the most frequently consumed rice every day (94%), eggs 3-4x/week (40%), tempeh 3-4x/week (40%), spinach 1-2x/week (64%), and bananas consumed 2-3x/day (2%) and 1-2x/week (54%). It can be concluded that the dietary habits of students majoring in nutrition in the Kepulauan Riau is still not diverse. Suggestions for nutrition students to improve their dietary habits by paying attention to the frequency, amount and type of food consumed.